2016
DOI: 10.1038/srep34241
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive switching analysis of Daphnia similoides between sexual female and parthenogenetic female by transcriptome comparison

Abstract: The water flea Daphnia are planktonic crustaceans commonly found in freshwater environment that can switch their reproduction mode from parthenogenesis to sexual reproduction to adapt to the external environment. As such, Daphnia are great model organisms to study the mechanism of reproductive switching, the underlying mechanism of reproduction and development in cladocerans and other animals. However, little is known about the Daphnia’s reproductive behaviour at a molecular level. We constructed a genetic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 54 publications
2
18
0
Order By: Relevance
“…In the present study, the expression levels of Vg gene and vitellogenin-2 gene were both significantly higher in SF compared to PF. Similar results were also reported in D. similoides ( Zhang et al, 2016 ). In addition, we also found that Dmagvtg1 was significantly up-regulated in SF at post-transcriptional level.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the expression levels of Vg gene and vitellogenin-2 gene were both significantly higher in SF compared to PF. Similar results were also reported in D. similoides ( Zhang et al, 2016 ). In addition, we also found that Dmagvtg1 was significantly up-regulated in SF at post-transcriptional level.…”
Section: Discussionsupporting
confidence: 91%
“…Isobaric tags for relative and absolute quantitation (iTRAQ) is the second generation of gel-free proteomic analysis that allows for a more accurate quantitation of proteins than low-throughput proteomic methods, such as traditional two-dimensional gel-based approaches. Recently, transcriptome analysis has been used to determine the DEGs between PF and SF in D. pulex ( Toyota et al, 2015 ) and D. similoides ( Zhang et al, 2016 ), respectively. However, as far as we know, there is no study to conduct proteomic profiling to examine the proteins involved in the reproductive switching under environmental stresses.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally assumed that the transition between sexual and asexual reproduction represents a major evolutionary change [ 46 ], potentially requiring a major molecular and cellular reorganization. Previous studies have indeed detected hundreds of genes that are differentially expressed between sexual and asexual lineages [ 16 ], or even between sexual and asexual parts of the life cycle of aphids and Daphnia [ 24 , 47 49 ]. In the light of this, it is surprising that we find few genes consistently associated with the transition from sexual to asexual reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…GO enrichment analysis of the differentially expressed genes (DEGs) was implemented using the GOseq R packages based on the Wallenius non-central hyper-geometric distribution [ 32 , 33 ], which can adjust for gene length bias in DEGs.…”
Section: Methodsmentioning
confidence: 99%